25.3k views
2 votes
-400=-6(8 - 8x) - 4x

1 Answer

0 votes

Answer:

The solution of -400 = -6(8 - 8x) - 4x is -8

Solution:

From question, the equation given is,

-400 = -6(8 - 8x) - 4x

Multiplying the terms inside the bracket with -6

-400 = -48 + 48x - 4x

On solving,

-400 = -48 + 44x

In the above equation, move -48 from right side to left side,

-400 + 48 = 44x

Now,

-352 = 44x

44x = -352

Now, the ‘x’ becomes,


x = (-352)/(44)

Thus, the value of the variable ‘x’ is:

x = -8

User Superdunck
by
4.9k points